A Conceptual View of Cognitive Intervention in Older Adults With and Without Cognitive Decline—A Systemic Review - Mendes, Liliana; Oliveira, Joana; Barbosa, Fernando; Castelo-Branco, Miguel (Frontiers in Aging, 2022)
Background: Dementia is the one of the most common and prominent disease in the elderly person that results in the Cognitive interventions. In this study, we aim to conceptualize the cognitive intervention for older adults with and without cognitive dysfunction and to clarify the heterogeneity existing in this literature field by determining the main variables implicated. Methods. We conducted a study analysis using previous literature highlighting the significant data reporting empirical results from cognitive intervention for healthy older adults and other seniors with different types of dementia. Each paper was reviewed in terms of compensatory cognitive training, cognitive remediation, enrichment, cognitive activation, brain training, cognitive stimulation, cognitive training, and cognitive rehabilitation. The research analysis was performed following rigorous inclusion and exclusion criteria with the purpose of collecting relevant answers to our research questions. Results. We included a total of 168 studies in our review. Our findings indicated heterogeneity regarding methods, concepts, and procedures. Additionally, the values were integrated using different information existing in this field. Conclusion: In conclusion, we highlighted that this is the first review that clarify the discrepancy of various existing definitions, methods, and procedures, as well as the overlapping information in the cognitive interventions.